Radiographic Study of Extraction Difficulty At Lower Third Molar Impacted Using The Pederson Assessment System - Supriyadi, Supriyadi -; Swasthi; Kartika Apriyono, Dwi (Jurnal Kesehatan Gigi, 2025)
The mandibular third molar (38/48) is the tooth with the highest prevalence of impact. Impacted teeth 38 and 48 often cause pathological complications that require extraction; and for that it is very important considering the level of difficulty. This study aims to determine the level of difficulty of extraction of the impacted third molar tooth through panoramic radiography using the Pederson Scoring System (PSS). This observational study involved 91 panoramic radiographs from patients > 20 years old with lower third molar teeth that had an impact at RSGMP University of Jember, patient data on radiographs is complete, coverage (region of interest / ROI) is sufficient and visual quality is good. The level of extraction difficulty was assessed using PSS, and categorized into low, medium and high. The data obtained were analyzed descriptively. This study used 144 impacted lower third molars from 91 patients; 61 from male and 83 from females; 73 teeth (50.69%) occurred in the right region and 71 teeth (49.31%) occurred in the left region. In male samples, 31 teeth (50.82%) occurred in the right region and 30 teeth (49.18%) occurred in the left region; Meanwhile, in the female sample, 43 teeth (51.81%) occurred in the right region and 40 teeth (48.19%) occurred in the left region. Based on PSS index, 4.86% had a low risk of extraction difficulty, 65.28% moderate and 29.86% high.The conclusion of this study is that the level of difficulty in extracting mandibular third molars at RSGMP Jember University is mostly (65%) moderate difficulty